Development of an out-of-Focus Irradiator Based on a Phased Antenna Array for a Space Communications' Parabolic Reflector Antenna - D. V. Douksha; S. V. Liashkevich; V. A. Saetchnikov (Приборы и методы измерений, 2019)
Mirror antenna systems are widely used in satellite and space communication systems and radio astronomy. Development of these areas requires new efficient antenna systems' design. Possible technical solution for creating an effective mirror antenna is a “hybrid” scheme, when an adaptive phased antenna array is used as an irradiator. This paper is devoted to the development of an out-of-focus irradiator based on a phased antenna array for a space communications' parabolic reflector antenna. The aim of the work is to develop an optimal design of the irradiator with the choice of the structural element of the antenna array and experimental studies of the selected structural element.The wavefront recovery method was used as a tool for selecting the irradiator configuration. The idea of this method use is to reproduce the electromagnetic field of an incident plane wave with an irradiator in order to uniformly illuminate the aperture of the antenna mirror.In order to select the structural element of the irradiator several antennas were considered: a patch antenna, a flat spiral antenna, a conical spiral antenna. The requirements for the phased antenna array element were defined. The irradiator based on the above mentioned was simulated and the irradiator geometry was optimized according to the maximum gain criterion.The maximum gain was achieved for the irradiator based on conical spiral antennas and amounted to 30.8 dB, which for the considered mirror aperture of 2.4 m is close to traditional focal schemes. The results obtained make it possible to create an adaptive antenna system able to compensate for the deviations of the mirror's shape from the theoretical profile, as well as phase distortions in the atmosphere by changing the lattice weights coefficients.